Application of the extended theory of planned behavior to predict green product purchase behavior - Wardana, Candra Kusuma; A'zizah, Laila Osiana Fitria; Abas, Novel Idris; Kusumawati, Rita (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
The importance of buying green products has been well publicized on social media. However, sales of green products remain considerably low. Marketers and academics aim to investigate the factors that influence green purchasing behavior. The aim of this paper is to examining the effect of attitude, subjective norms, perceived behavioral control, on green purchase intention. Because there is attitude-behavior gap, this study also provides a meaningful contribution by extending the Theory of Planned Behavior by incorporating social media marketing, environmental knowledge, and green product purchase behavior. A quantitative approach was used to collect data through online questionnaires. A total of 249 samples were analyzed using structural equation modeling (SEM) with Smart PLS. The results align with existing literature, reinforcing the importance of attitude, perceived behavioral control, social media marketing, and environmental knowledge in shaping consumers’ intentions and behaviors. However, subjective norm does not significantly perform as a direct antecedent on purchase intention. Social pressure is not enough to drive consumer purchasing environmentally products. These results can assist business owners and social media marketers to focus on promoting green image and continuously produce educative content which could enhance people awareness on the importance of green product consumption.